Effectiveness of Tongue Crib Combination Treating Severe Skeletal Angle Class III Malocclusion in Mixed Dentition - Zhao, Wenting (Int J Clin Pediatr Dent, 2020)
OBJECTIVE: To evaluate the treatment effects of tongue crib combination for treating severe skeletal Angle class III malocclusion in mixed dentition by X-ray cephalometric analysis. MATERIALS AND METHODS: A sample of 22 patients with severe skeletal Angle class III malocclusion of deficiency maxilla and overgrown mandible in mixed dentition was prospectively collected and equally divided into two groups. The patients (males 6 and females 5; mean age 8.35 ± 1.6 years) in the study group were treated with tongue crib combination, and the untreated patients (females 5, males 6; mean age 8.12 ± 1.3 years) served as the control group. X-ray cephalometric films were measured before and after treatment for comparing the change of occlusion, maxilla, mandible, and soft tissue. A paired t-test was used by SPSS 21.0 statistical software. The intragroup data were compared by using the Wilcoxon test, and intergroup data were compared by using the Mann–Whitney U test (p < 0.05). RESULTS: In the study group, all patients got a favorable facial profile. Anterior and posterior teeth crossbite and upper and lower first molars relationships were improved. In cephalometric measurement, significant changes were noted in the maxillary skeletal component. The significant forward growth of the maxilla exhibited in a statistical increase of SNA, ANS-PNS, Wits appraisal, p < 0.05. The mandible revealed slightly posterior rotation by no significant decrease in SNB and no change Co-Gn. After 1-year of retention, the changes of the teeth showed self-correction and facial profile improved further. Regarding vertical changes, maintenance of growth was shown a small non-significant increase of FMA, N-Me, and ANS-Me. There is a significant difference from those in the control group (p < 0.05). CONCLUSION: Tongue crib combination is an effective device for the patients in the growing period with skeletal Angle class III malocclusion by improving the maxillary growth and limiting the mandibular growth. HOW TO CITE THIS ARTICLE: Zhao W, Chen Y, Kyung H-M, et al. Effectiveness of Tongue Crib Combination Treating Severe Skeletal Angle Class III Malocclusion in Mixed Dentition. Int J Clin Pediatr Dent 2020;13(6):668–676.